An Analysis of Moral Values on Rita Hayworth and Shawshank Redemption Chapter in Different Seasons Novel - Rezeki, Merry Sri; Susilawati, Endang; Rosnija, Eni (Lingual Journal of Language and Culture; Vol 16 No 2 (2023): Lingual: Journal of Language and Culture, 2023)
This research focuses on how to analyze the moral values contained in the novel Different Seasons: Rita Hayworth and Shawshank Redemption with special emphasis on the main character, Andy Dufresne. The purpose of this research is to identify moral values through dialog with the main characters or conflicts faced and reveal the moral values that arise from efforts to overcome conflicts. This research uses descriptive qualitative method and uses moral value theory by Burhan Nurgiyantoro (2013) in analyzing the data obtained in the novel. The main character in this novel faces many conflicts and also interacts with other characters. The main character overcomes these problems by demonstrating the moral value of helping other humans and showing compassion. This study found six moral values of human relationships with other humans in several aspects, such as to sense humankind and to be helpful to individuals.